Authorea
DOI: 10.22541/au.158212862.25725074
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent life history and transcriptomic responses in heat-tolerant versus heat-sensitive Brachionus rotifers

Abstract: A species' response to thermal stress is an essential physiological trait that can determine occurrence and temporal succession in nature, including response to climate change. Environmental temperature affects zooplankton performance by altering life-spans and population growth rates, but the molecular mechanisms underlying these alterations are largely unknown. To compare temperature-related demography, we performed cross-temperature life-table experiments in closely related heat-tolerant and heat-sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 64 publications
(90 reference statements)
2
11
0
Order By: Relevance
“…Our Papakostas et al, 2016;Paraskevopoulou et al, 2020Paraskevopoulou et al, , 2018Zhang et al, 2019). On the other hand, they support earlier conclusions that these species do hybridize (Lemmen et al, 2020;Papakostas et al, 2016) providing a plausible explanation for frequently observed mitonuclear discordances in field populations (Papakostas et al, 2016;Zhang et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Our Papakostas et al, 2016;Paraskevopoulou et al, 2020Paraskevopoulou et al, , 2018Zhang et al, 2019). On the other hand, they support earlier conclusions that these species do hybridize (Lemmen et al, 2020;Papakostas et al, 2016) providing a plausible explanation for frequently observed mitonuclear discordances in field populations (Papakostas et al, 2016;Zhang et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…However, it is becoming increasingly clear that this is not the case and that the expression of RPs can change in response to a number of different factors, e.g. heat stress (Paraskevopoulou et al, 2020) or the ingestion of ribosome-inactivating proteins (RIPs) contained in plant material (Celorio-Mancera et al, 2013;Stirpe, 2013). RPs also play numerous roles outside of ribosomal biogenesis (Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Larvae that were starved but whose parents were not starved may have suffered more than starved larvae from starved parents, as indicated by the upregulation of putative ribosomal pathway genes. Differential expression of genes of the ribosomal pathway has been observed in a wide variety of taxa in response to thermal stress (Paraskevopoulou et al 2020; Schwanz et al 2020; Srikanth et al 2020), demonstrating the broad role of this pathway in stress response. Differential expression of genes involved in stress and other physiological and metabolic responses may have energetic costs, which may lead to a prolonged development time of starved larvae in A. rosae .…”
Section: Discussionmentioning
confidence: 99%